2017
DOI: 10.1111/gfs.12310
|View full text |Cite
|
Sign up to set email alerts
|

Modelling pasture production and soil temperature, water and carbon fluxes in Mediterranean grassland systems with the Pasture Simulation model

Abstract: Grasslands play important roles in agricultural production and provide a range of ecosystem services. Modelling can be a valuable adjunct to experimental research in order to improve the knowledge and assess the impact of management practices in grassland systems. In this study, the PaSim model was assessed for its ability to simulate plant biomass production, soil temperature, water content, and total and heterotrophic soil respiration in Mediterranean grasslands. The study site was the extensively managed sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 50 publications
2
12
1
Order By: Relevance
“…Accounting for additional factors and their integration in grassland models, however, needs careful consideration in terms of potential changes in model behavior [48], especially when moving to other ecoregions (e.g. Mediterranean grasslands characterized by shifted growing-seasons to autumn-spring, summer drought and variable precipitation [49]). While the GRASSMIND model simulates the biogeochemical growth of individual plants interacting with each other in their neighborhood, other comparable grassland models simplify specific processes in favor of applicability [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accounting for additional factors and their integration in grassland models, however, needs careful consideration in terms of potential changes in model behavior [48], especially when moving to other ecoregions (e.g. Mediterranean grasslands characterized by shifted growing-seasons to autumn-spring, summer drought and variable precipitation [49]). While the GRASSMIND model simulates the biogeochemical growth of individual plants interacting with each other in their neighborhood, other comparable grassland models simplify specific processes in favor of applicability [15].…”
Section: Discussionmentioning
confidence: 99%
“…Accounting for additional factors and their integration in grassland models, however, needs careful consideration in terms of potential changes in model behavior [ 48 ], especially when moving to other ecoregions (e.g. Mediterranean grasslands characterized by shifted growing-seasons to autumn-spring, summer drought and variable precipitation [ 49 ]).…”
Section: Discussionmentioning
confidence: 99%
“…However, the maximum grass growth was estimated at 30 AGDD before what was observed in the field. Pulina et al [35] suggested that these differences could be attributed to the sensitivity of the models to extreme values during data collection.…”
Section: Grass Growthmentioning
confidence: 99%
“…Developing grazing ecosystem models can effectively support efforts to improve productivity and enhancing ecosystem services while tackling climate change impacts. Many process-based models have been developed for grazing lands, such as the Pasture Simulation model (PaSim) [67], NGAUGE [68], Denitrification Decomposition (DNDC) [26,69], DayCent [28], Roth-C [70]. Here, we do not to perform a full review of various agroecosystem models but illustrate some common approaches of simulating grazing lands through several typical BGC-AES models.…”
Section: Biogeochemical -Agroecosystem (Bgc-aes) Modelsmentioning
confidence: 99%